1995
DOI: 10.1002/mrm.1910330502
|View full text |Cite
|
Sign up to set email alerts
|

Localized proton NMR spectroscopy in the striatum of patients with idiopathic parkinson's disease: a multicenter pilot study

Abstract: Please be advised that this information was generated on 2018-05-08 and may be subject to change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
59
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 32 publications
5
59
1
Order By: Relevance
“…(1998) demonstrated reduced NAA/Cr in PD patients and Holshouser et al. (1995) demonstrated significantly reduced NAA/Cho ratio in PD patients, and researchers have demonstrated that the level of NAA may reflect the status of neuron function. Specifically, reduced NAA level may represent reduced number of neurons or neuron deficiency, whereas a decreased NAA level reflects severe neurodegeneration and motor impairment (Sharma et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1998) demonstrated reduced NAA/Cr in PD patients and Holshouser et al. (1995) demonstrated significantly reduced NAA/Cho ratio in PD patients, and researchers have demonstrated that the level of NAA may reflect the status of neuron function. Specifically, reduced NAA level may represent reduced number of neurons or neuron deficiency, whereas a decreased NAA level reflects severe neurodegeneration and motor impairment (Sharma et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Our results fall in line with earlier neuroimaging 1 H‐MRS studies, showing reduced NAA/Cr ratio in the temporoparietal cortex (Hu et al., 1999) and motor cortex (Lucetti et al., 2001). However, there are single‐volume 1 H‐MRS gave conflicting results, which failed to demonstrate significant NAA/Cr ratio change in the striatum (Holshouser et al., 1995) and significant NAA/Cho ratio change in the occipital cortices (Tedeschi et al., 1997). The discrepancy can be explained in part by the difference in study population and sample size and the region of interest in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when patients were grouped based on clinical criteria, neural networks could be trained to classify spectra into these groups and controls to a relatively high degree. Published 1 H MRS results suggest that there are generally no dramatic differences in metabolite concentrations between PD patients and controls (5)(6)(7)(8)23,24). Furthermore, where differences do exist, they are frequently not sufficient to enable classification of individuals from a data set of patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo 1 H MRS has been used to investigate brain metabolism in PD by several groups (5)(6)(7)(8)(9). In vivo 1 H MRS data are most often analyzed by conventional statistical methods.…”
mentioning
confidence: 99%
“…Other 1 H-MRS examinations didn't show significant difference between the PD patients and the control subjects (Tedeschi et al, 1997), also in the striatum (Holshouser et al, 1995), in the putamen and globus pallidus (Federico et al, 1997), and in occipital lobe (Bowen et al, 1995). The NAA/Cho and NAA/Cr ratios were significantly reduced in the putamen and globus pallidus of MSA and the PSP patients, in which neuronal loss involves, compared with the control subjects (Federico et al, 1997).…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 95%